2002
DOI: 10.1136/bjsm.36.4.304
|View full text |Cite
|
Sign up to set email alerts
|

Are there differences in postural regulation according to the level of competition in judoists?

Abstract: The aim of this work was to study the posturokinetic capacities and use of visual information by judoists according to their level of competition. Twenty male judoists aged between 16 and 19 took part. They were separated into two groups: those that competed at regional level and those that competed at national and international level. Static balance was measured on a force platform. No difference was seen between the two groups. However, it seems that visual information is more important to the higher level j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
104
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 5 publications
18
104
3
4
Order By: Relevance
“…[4,6] The most prevalent laboratory test for static balance is monitoring the centre of pressure (CoP) motion for a specified duration as an athlete attempts to stand motionless on a force platform, unipedal or bipedal, eyes open or eyes shut. [7][8][9] While it is acknowledged that CoP motion is not identical to CoG motion [10] , minimal CoP motion is indicative of good balance and CoP measured from a force platform is generally considered the gold standard measure of balance. [11] Examples of field tests of dynamic balance include unipedal stance on a wobble board and counting the number of floor contacts in 30s [12] and the Star Excursion Balance…”
Section: Static and Dynamic Balancementioning
confidence: 99%
See 1 more Smart Citation
“…[4,6] The most prevalent laboratory test for static balance is monitoring the centre of pressure (CoP) motion for a specified duration as an athlete attempts to stand motionless on a force platform, unipedal or bipedal, eyes open or eyes shut. [7][8][9] While it is acknowledged that CoP motion is not identical to CoG motion [10] , minimal CoP motion is indicative of good balance and CoP measured from a force platform is generally considered the gold standard measure of balance. [11] Examples of field tests of dynamic balance include unipedal stance on a wobble board and counting the number of floor contacts in 30s [12] and the Star Excursion Balance…”
Section: Static and Dynamic Balancementioning
confidence: 99%
“…[13] There are other sports where it might be expected that more proficient athletes would display better balance but this was not found for different competition levels for alpine skiing, surfing and judo. [8,33,35] National and international level alpine skiers had similar static and dynamic bipedal balance to regional level skiers when tested with ski boots but inferior bare foot static and dynamic balance to regional skiers. [33] To explain this unexpected result, it was proposed that elite skiers spend more time in ski boots and possibly don't get as much postural control conditioning of the ankle-foot complex.…”
Section: Comparison Of Balance Ability Of Athletes At Different Levelmentioning
confidence: 99%
“…Nagy et al 21 also found lower dependence to eyesight in the ironman athletes compared with individuals who performed other type of regular physical activity. Nevertheless, Paillard et al 22 showed that more experienced judo fighters are more dependent to eyesight than less experienced ones.…”
Section: Instrumentsmentioning
confidence: 91%
“…This constitutes the base for the correct execution of complex technical gestures, as well as for the minimization of injury risks. The importance of balance monitoring in adult athletes clearly appears from the conclusions of both articles by (Paillard, 2002) and (Paillard, 2006), the first one regarding judoists, and the second one regarding soccer players balance analysis. Results show that no differences in static balance are evident for judoists performing at regional level and judoists performing at national and international level.…”
Section: The Importance Of Balance Monitoring and Improvement In Younmentioning
confidence: 99%